A report of transcatheter aortic valve insertion in a patient with chronic type B aortic dissection. Issue 2 (6th January 2021) - Schumer, Erin M.; Eleid, Mackram F.; Greason, Kevin L.
Abstract: A 72‐year‐old man presented with symptomatic, severe aortic valve stenosis and a chronic descending thoracic aorta dissection with descending thoracic aortic aneurysm. After careful consideration, a transcatheter aortic valve was inserted through a transfemoral approach. This case demonstrates feasibility, and consideration should be given to this approach in patients requiring intervention for aortic stenosis.